(untitled) (Research, Society and Development, 2021)
Objective: to reflect on the challenges for the teaching practice of nursing in higher education. Methodology: this is a reflective study, based on Brazilian and international scientific literature. It is based on three thematic sections: i) The construction of the professional identity of the teacher in higher education; ii) The pedagogical formation of the teacher in nursing in higher education; iii) The dichotomy between teaching and care. Results: entry into higher education teaching is surrounded by various challenges, such as the construction of professional identity, the pedagogical training process and the dichotomy between teaching and care. Training in this area does not guarantee sufficient tools to act as a teacher, characterizing themes that urgently require discussions on the requirements for this professional field. Final Considerations: the indispensability of training processes that guarantee preparation for the various complexities involved in educating and training professionals for higher education is evident. Therefore, this reflection contributes adding pertinent information which may help in scientific formations and permanent education for the reorganization of concepts and ideas linked to the challenges for the practice of the teacher in nursing in higher education.